2021
DOI: 10.1016/j.reth.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Repair of spinal cord injury in rats via exosomes from bone mesenchymal stem cells requires sonic hedgehog

Abstract: Objective The loss of neural ability leading to subsequent diminishing of motor function and the impairment below the location of the injury is a result of the SCI (Spinal Cord Injury). Among the many therapeutic agents for SCI, the exosomes considered as extracellular vesicles seem to be the most promising. Sonic Hedgehog (Shh) is an exosome-carrying protein. This Study's purpose was to identify whether Shh is required for exosomes from BMSCs (mesenchymal stem cells of the bone) and plays a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Among the included 32 studies, only two studies were controlled studies ( 29 , 33 ), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats ( 19 21 , 28 37 , 39 , 40 , 42 44 , 46 , 47 , 49 53 , 55 , 56 ), Wistar rats ( 41 , 54 ), and C57BL/6 mice ( 38 , 45 , 48 ); gender included male ( 28 , 30 32 , 38 45 , 49 , 53 , 54 ) and female ( 19 , 20 , 29 , 33 , 34 , 36 , 37 , 46 48 , 50 52 , 55 , 56 ), two studies did not report the sex of the animals ( 21 , 35 ); the weights of animals were between 150 ( 41 ) and 300 g ( 20 , 44 ), the weight of the mouse was between 17 and 22 g ( 48 ), and seven of the studies did not report the weight of the animals ( 21 , 29 , 30 , 38 , 42 , 45 , 50 ); age was between 6 ( 38 , 44 , 45 , 50 , 51 ) and 12 weeks ( 47 , 56 ), and nine of the studies did not report the age of the animals ( …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the included 32 studies, only two studies were controlled studies ( 29 , 33 ), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats ( 19 21 , 28 37 , 39 , 40 , 42 44 , 46 , 47 , 49 53 , 55 , 56 ), Wistar rats ( 41 , 54 ), and C57BL/6 mice ( 38 , 45 , 48 ); gender included male ( 28 , 30 32 , 38 45 , 49 , 53 , 54 ) and female ( 19 , 20 , 29 , 33 , 34 , 36 , 37 , 46 48 , 50 52 , 55 , 56 ), two studies did not report the sex of the animals ( 21 , 35 ); the weights of animals were between 150 ( 41 ) and 300 g ( 20 , 44 ), the weight of the mouse was between 17 and 22 g ( 48 ), and seven of the studies did not report the weight of the animals ( 21 , 29 , 30 , 38 , 42 , 45 , 50 ); age was between 6 ( 38 , 44 , 45 , 50 , 51 ) and 12 weeks ( 47 , 56 ), and nine of the studies did not report the age of the animals ( …”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported types of exosomes but did not report specific sources ( 31 , 32 , 38 , 40 , 45 , 46 ). The transplantation route of exosomes included tail vein ( 19 21 , 29 32 , 34 50 , 52 – 56 ), intranasally ( 33 ) and subcutaneous ( 51 ), and one study did not report the route of exosome transplantation ( 28 ); the time transplantation of exosome ranged from 0 ( 19 , 20 , 31 , 38 , 41 , 44 47 , 49 ) to 24 h ( 42 , 43 ) after modeling, one study did not report the time of exosome transplantation ( 40 ); dose of exosomes ranged from 20 ( 29 ) to 200 μg ( 28 , 30 33 , 36 38 , 41 , 43 , 45 49 , 53 , 56 ); the control group includes PBS ( 19 21 , 28 32 , 34 , 35 , 38 , 39 , 41 , 43 51 , 53 – 56 ), saline ( 33 , 36 , 37 , 40 , 42 ), and blank ( 52 ). Basic information of the study subjects was summarized in Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, recent findings are ascribing Shh a crucial role in the neuroregeneration after CNS injuries [ 32 , 33 , 34 , 35 ]. New evidence even suggests that the activation of the Shh-pathway may be necessary to enable MSC-derived exosome mediated SCI repair [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs-Exos were separated and concentrated by ultracentrifugation and differential centrifugation in many studies (Huang et al, 2017 , 2020a ; Lankford et al, 2018 ; Wang et al, 2018 ; Guo et al, 2019 ; Ji et al, 2019 ; Kang et al, 2019 ; Li et al, 2019 ; Li C. et al, 2020 ; Li et al, 2021 ; Chen et al, 2021 ; Cheng et al, 2021 ; Han et al, 2021 ; Jia et al, 2021 ; Jiang and Zhang, 2021 ; Liu W. Z. et al, 2021 ; Liu et al, 2022 ; Nakazaki et al, 2021 ; Nie and Jiang, 2021 ; Noori et al, 2021 ; Sheng et al, 2021 ; Xiao et al, 2021 ; Xin et al, 2021 ; Zhang A. et al, 2021 ; Liang et al, 2022 ; Zhou et al, 2022 ) and by precipitation kits/polymer (PEG or others) in some studies (Li et al, 2018 ; Ren et al, 2019 ; Xu et al, 2019 ; Yu et al, 2019 ; Zhao et al, 2019 ; Fan et al, 2021 ; Jia et al, 2021a , b ; Kang and Guo, 2022 ). To achieve better specificity of MSCs-Exos separation, many researchers isolated MSCs-Exos using ultrafiltration-centrifugation combined with density-gradient ultracentrifugation (Liu et al, 2020 ; Shao et al, 2020 ; Chang et al, 2021 ; Luo et al, 2021 ; Huang et al, 2022 ).…”
Section: The Separation and Concentration Methods Of Each Cell-derive...mentioning
confidence: 99%